2023
DOI: 10.24853/ijbesr.7.1.1-6
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Socio-Cultural Aspects and the Physical Setting of Muncar Coastal Settlement

Abstract: Muncar has been developed into a core Minneapolitan area since 2012. The development of the Minneapolitan area can affect the socio-cultural aspects of the fishing community which then affects the physical setting of the coastal settlement, which is actually part of the ekistics elements of the settlement.  This research aims to examine the relationship of the socio-cultural aspects of the Muncar fishing community especially in Sampangan Hamlet to the condition of its physical setting which is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Several studies focus on art objects in coastal settlements of Central Java: ornamental designs in Javanese coastal mosques (Robson, 1981), colorful coastal batik (Idham, 2018), Buraq puppet from coastal Brebes, Central Java (Triyanto et al, 2016), and art education (Setyobudi, 2018). One study discusses coastal settlements in Banyuwangi, East Java, and one study in Bandung, West Java (Cayarini, Nugroho & Asikin, 2023;Heriyawati & Wita, 2022). All of these studies have shown consistent evidence that coastal settlements have had a strong influence on the shaping and development of Javanese vernacular art.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies focus on art objects in coastal settlements of Central Java: ornamental designs in Javanese coastal mosques (Robson, 1981), colorful coastal batik (Idham, 2018), Buraq puppet from coastal Brebes, Central Java (Triyanto et al, 2016), and art education (Setyobudi, 2018). One study discusses coastal settlements in Banyuwangi, East Java, and one study in Bandung, West Java (Cayarini, Nugroho & Asikin, 2023;Heriyawati & Wita, 2022). All of these studies have shown consistent evidence that coastal settlements have had a strong influence on the shaping and development of Javanese vernacular art.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In terms of coastal settlements, there are several research that discuss their connection with the creation of art and culture. Cayarini, Nugroho & Asikin (2023) have said that settlement patterns, building orientation directions, landform changes, gender-based space utilization, and cultural spaces in coastal settlements are influenced by socio-cultural aspects. Similarly, Setyobudi (2018) has stated that Javanese cultural characteristics in coastal settlements are oriented towards Islamic values that can be utilized for student character building through art education for elementary to junior high school students.…”
Section: Review Of Literaturementioning
confidence: 99%